Structural Decomposition of Residential Property Prices in Indonesia: a VAR Approach - Naveed Aslam; Mahrus Lutfi Adi Kurniawan; Wisnu Hammam Pratama (Journal of Asset Management and Public Economy (JAMPE), 2023)
Home ownership is so important for human survival. the Residential Property Price Index or IHPR increases every time. It is feared that the continuous increase in house prices exceeding their fundamental value will lead to a property bubble like the one that hit the United States in 2008. This study contributes to look at the IHPR's response to shocks from inflation. BI interest rate, GDP, compensation index for permanent workers and Construction Daily Worker and Construction IHPB. Using time-series data from 2010Q1-2021Q4 and the VAR method shows that the IHPR responds positively to changes in the shock of the inflation variable, the compensation index for permanent workers and construction daily workers and the WPI for Construction. Meanwhile, the IHPR response negatively to changes in interest rates and GDP. Based on the results of the variance decomposition. the construction IHPB is the variable that contributes the most. namely 12.2% to changes in IHPR.  Implication of the research to maintain the macroeconomic condition to courage the IHPR on stabil condition.